MEANING ON TRANSLATION OF INDONESIAN-ENGLISH ADS TEXT - Purwani Indri Astuti (University of Kuningan, 2017)
This research was actually about the meaning of translation in Indonesian-English ads text, the booklet of PUD in Sukoharjo regency. Translating ads text is not simple because ads text has certain structure to be fulfilled. Then, to translate some cultural terms in ads text, it needs some considerations to keep the quality of the translation itself. One of the considerations is about the concept of readibility that consists of length of sentence average,Â new words, and grammatical complexity. The research belonged to qualitative research andÂ the data were all the phrases and the sentences in the booklet of PUD Sukoharjo regency. The methods of data collecting were questionaire, in-depth interview, and content analysis with the instrumens of questions, interview guides, and data card. The data were then analyzed by using Miles and Huberman interactive model while the data validity was data triangulation. The result of the research showed that the readibility of Indonesian-English ads text was rather low for the score of the readibilty rating instrument was 2.2 from the total score of 3.Keywords: translation, ads text, readibility